Biotechnological Interventions for Reducing the Juvenility in Perennials - Pooja Manchanda; Maninder Kaur; Shweta Sharma; Gurupkar Singh Sidhu (Horticulturae, 2022)
During shoot apex development, the plants undergo a very complex transition phase of flowering for successful reproduction, seed/cone setting and fruit development. The conversion of vegetative shoot meristems to floral meristems depends upon numerous endogenous, exogenous factors and flowering genes for the development of floral parts. The perennial crops suffer from the limitation of the innate ability to keep some meristems in the vegetative state for the polycarpic growth habit leading to the long juvenile phase. Conventional breeding approaches viz. selection of early flowering parental lines, flower thinning and grafting are time-consuming requiring more time for the release of a new cultivar which is undesirable for rapid crop improvement. The best way to accelerate the perennial plant breeding improvement programs and to reduce the long juvenile phase is the induction of early flowering through the utilization of biotechnological approaches. The ability to allow the transmission of an early flowering gene to the progeny in a Mendelian fashion is the major advantage of biotechnological interventions. The introgression of early flowering traits from non-commercial germplasm or sexually compatible species to perennial species through the biotechnological aspects will act as a boon for crop improvement in future studies. The present review gives an overview of various flowering genes in perennial crops accompanying the implementation of biotechnological approaches including overexpression studies, RNA interference, Virus-induced flowering and CRISPR-Cas approaches that will help in reducing the period for induction of flowering in perennial crops.